RETRACTED: Works of art and culture in the architectural and landscape environment of the historical part of Rostov-on-Don, Russia, in the formation of the personality of youth - Goryacheva Elena; Vlasova Irina; Lukyanov Rafael (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001